Large scale calcium channel gene rearrangements in episodic ataxia and hemiplegic migraine: implications for diagnostic testing. Issue 11 (7th July 2009) - Labrum, R W; Rajakulendran, S; Graves, T D; Eunson, L H; Bevan, R; Sweeney, M G; Hammans, S R; Tubridy, N; Britton, T; Carr, L J; Ostergaard, J R; Kennedy, C R; et al.
Abstract : Background: Episodic ataxia type 2 (EA2) and familial hemiplegic migraine type 1 (FHM1) are autosomal dominant disorders characterised by paroxysmal ataxia and migraine, respectively. Point mutations in CACNA1A, which encodes the neuronal P/Q-type calcium channel, have been detected in many cases of EA2 and FHM1. The genetic basis of typical cases without CACNA1A point mutations is not fully known. Standard DNA sequencing methods may miss large scale genetic rearrangements such as deletions and duplications. The authors investigated whether large scale genetic rearrangements in CACNA1A can cause EA2 and FHM1. Methods: The authors used multiplex ligation dependent probe amplification (MLPA) to screen for intragenic CACNA1A rearrangements. Results: The authors identified five previously unreported large scale deletions in CACNA1A in seven families with episodic ataxia and in one case with hemiplegic migraine. One of the deletions (exon 6 of CACNA1A ) segregated with episodic ataxia in a four generation family with eight affected individuals previously mapped to 19p13. In addition, the authors identified the first pathogenic duplication in CACNA1A in an index case with isolated episodic diplopia without ataxia and in a first degree relative with episodic ataxia. Conclusions: Large scale deletions and duplications can cause CACNA1A associated channelopathies. Direct DNA sequencing alone is not sufficient as a diagnostic screening test.